The NDR family of kinases: essential regulators of aging - Jonischkies, Kevin; del Angel, Miguel; Demiray, Yunus Emre; Loaiza Zambrano, Allison; Stork, Oliver (Frontiers in Molecular Neuroscience, 2024)
Aging is defined as a progressive decline of cognitive and physiological functions over lifetime. Since the definition of the nine hallmarks of aging in 2013 by López-Otin, numerous studies have attempted to identify the main regulators and contributors in the aging process. One interesting group of proteins whose participation has been implicated in several aging hallmarks are the nuclear DBF2-related (NDR) family of serine-threonine AGC kinases. They are one of the core components of the Hippo signaling pathway and include NDR1, NDR2, LATS1 and LATS2 in mammals, along with its highly conserved metazoan orthologs; Trc in Drosophila melanogaster, SAX-1 in Caenorhabditis elegans, CBK1, DBF20 in Saccharomyces cerevisiae and orb6 in Saccharomyces pombe. These kinases have been independently linked to the regulation of widely diverse cellular processes disrupted during aging such as the cell cycle progression, transcription, intercellular communication, nutrient homeostasis, autophagy, apoptosis, and stem cell differentiation. However, a comprehensive overview of the state-of-the-art knowledge regarding the post-translational modifications of and by NDR kinases in aging has not been conducted. In this review, we summarize the current understanding of the NDR family of kinases, focusing on their relevance to various aging hallmarks, and emphasize the growing body of evidence that suggests NDR kinases are essential regulators of aging across species.